اسلام میں مردو خواتین میں فرق و امتیاز کا مسئلہ:اسلامی اصول و ضوابط کی حکمتوں کا مطالعہ: Issue of Discrimination between Men and Women in Islam: A Study of the Wisdom behind Islamic Principles - Hafiza bareera Hameed; Dr. Abul Hassan Shabbir Ahmad (Al-Qamar, 2020)
Some people claim that Islam is unjust towards women in giving her half of what men receive. This article exploring the wisdom behind the differences in Islamic principles regarding men and women in inheritance, blood money, legal testimony and headship of the state, concludes that it is impossible to have absolute equality between men and women in what is specific for each of them. Differences in this regard are understandable because men and women are different physiologically and psychologically. What Islam has established for women is that which suits their nature, gives them full security and protects them against disgraceful circumstances.